Economic impact of switching from metoprolol to nebivolol for hypertension treatment: a retrospective database analysis. (October 2014) - Chen, Stephanie; Tourkodimitris, Stavros; Lukic, Tatjana
Abstract Objective: To estimate the real-world economic impact of switching hypertensive patients from metoprolol, a commonly prescribed, generic, non-vasodilatory β1-blocker, to nebivolol, a branded-protected vasodilatory β1-blocker. Methods: Retrospective analysis with a pre–post study design was conducted using the MarketScan database (2007–2011). Hypertensive patients continuously treated with metoprolol for ≥6 months (pre-period) and then switched to nebivolol for ≥6 months (post-period) were identified. The index date for switching was defined as the first nebivolol dispensing date. Data were collected for the two 6-month periods pre- and post-switching. Monthly healthcare resource utilization and healthcare costs pre- and post-switching were calculated and compared using Wilcoxon test and paired t-test. Medical costs at different years were inflated to the 2011 dollar. Results: In total, 2259 patients (mean age: 60 years; male: 52%; cardiovascular [CV] disease: 37%) met the selection criteria. Switching to nebivolol was associated with statistically significant reductions in the number of all-cause hospitalization (−33%; p < 0.01), CV-related hospitalizations (−60%; p < 0.01), and outpatient visits (−7%; p < 0.01). Monthly inpatient costs were reduced by $111 (p < 0.01), while monthly drug costs increased by $52 (p < 0.01). No statistically significant differences were found in overall costs and costs of outpatient or ER visits. Sensitivity analyses, conducted using various lengths of medication exposure, controlling for spill-over effect or excluding patients with compelling indications for metoprolol, all found some level of reduction in resource utilization and no significant difference in overall healthcare costs. Conclusions: This real-world study suggests that switching from metoprolol to nebivolol is associated with an increase in medication costs and significant reductions in hospitalizations and outpatient visits upon switching, resulting in an overall neutral effect on healthcare costs. These results may be interpreted with caution due to lack of a comparator group and confounding control caused by design and limitations inherent in insurance claims data.